Make the Economy Scream? Economic, Ideological and Social Determinants of Support for Salvador Allende in Chile, 1970-3 - Osorio-Flores, R (CAMBRIDGE UNIV PRESS, 2017)
With polling and municipal level data, we analyse the determinants of Salvador Allende s presidential election victory in 1970 and the change in political and electoral support for his government (1970-3). Support for Allende is explained by ideology more than by social class, socio-demographic variables or the economic performance of the country. Allende won in 1970 as an opposition candidate when the outgoing Frei administration enjoyed high approval and the country was experiencing favourable economic conditions. In 1973, when Allende had 49.7% approval, ideology remained the strongest determinant of presidential approval. Economic variables and social class are less important in explaining electoral support for Allende and for his Popular Unity coalition.